Giving Soursop Leaf Extract (Annona Muricata L) to Lower Blood Pressure for Patients with Hypertension - Ayunita, Dian; Supodo, Timbul; Akbar Torontju, Sultan (Waluya The International Science of Health Journal, 2023)
Backgrounds: In Muna Regency, if we look at the prevalence of hypertension incidence data in Katobu District with a population of 31,929 people. In 2016 it was known that the prevalence of hypertension was 80 cases per thousand population, in 2017 there were 145 cases per thousand population, in 2018amounted to 143 cases per thousand population, in 2019 there were 145 cases per thousand population and in 2020 there were 130 cases per thousand population. Based on this, it is interesting for researchers to conduct research on Giving Soursop Leaf Extract (Annona Muricata L) To Lower Blood Pressure For Patients With Hypertension. Methods: The type of research conducted is pre-experimental research with a Pretest-Posttest design. The research was carried out in the working area of ​​the Katobu Public Health Center from April to June 2022 totaling 56 people with a sample of 49 people. Results: The average hypertension decreased in the first week 177.24, the second week 171.73 and the third week after administration of soursop leaf extract 171.19, the difference in blood pressure reduction of the three treatment groups. Judging from the ANOVA table, the column Sig. obtained P value (P-value) = 0.000. Conclusion: There is a significant effect between the administration of soursop leaf extract on reducing blood pressure in patients with hypertension in the working area of ​​the Katobu Public Health Center, Muna Regency.